Role of myocyte enhancing factor 2B in epithelial myofibroblast transition of human gingival keratinocytes - Sun, Qiang; Sattayakhom, Apsorn; Backs, Johannes; Stremmel, Wolfgang; Chamulitrat, Walee (Experimental biology and medicine, 2012)
It has recently emerged that the myogenic contribution of the epithelial mesenchymal transition plays a role in neoplastic invasion and metastasis. Myocyte enhancing factor 2B (MEF2B) is the only MEF2 isoform expressed during early embryonic development, and is herein proposed to transactivate the downstream target proteins of the epithelial myofibroblast transition (EMyT). We have previously generated eight preneoplastic cell lines with spindle and cobblestone morphology from human gingival mucosal keratinocytes immortalized by E6/E7 of human papillomavirus type 16. Spindle cells formed tubulogenic morphogenesis on Matrigel and exhibited contractility, anchorage-independent growth and invasiveness to a greater extent than cobblestone cells. Expression of MEF2B mRNA and myofibroblast proteins was higher in spindle cells compared with cobblestone cells. Epidermal growth factor (EGF) treatment of cobblestone cells also induced expression of these genes. Knockdown of MEF2B in a cobblestone cell line abolished EGF-induced upregulation of MEF2, vimentin and non-muscle caldesmon proteins, but enhanced basal expression of mesenchymal vimentin and fibronectin. Differential regulation of intermediate filaments revealed an unrecognized role of MEF2B in myogenic transformation of the epithelial to a myofibroblast phenotype, which occurs as epithelioid variants in some soft tissue sarcomas.